Edukasi Metode Cara Menulis Artikel Kuantitatif dan Kualitatif untuk Mahasiswa Pascasarjana - Primadi Candra Susanto; Sri Yanthy Yosepha (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Writing scientific articles is an important skill in the academic world that requires a deep understanding of research methods, both quantitative and qualitative. This article aims to provide education regarding article writing methods based on these two approaches. In quantitative methods, focus is given to the use of numerical data, statistical analysis, and generalization of research results. Meanwhile, qualitative methods focus on in-depth exploration of social phenomena, narrative data collection, and subjective interpretation. This article outlines the systematic steps in writing articles for both methods, starting from problem formulation, literature review, research design, and data analysis, to drawing up conclusions. By understanding the characteristics and structure of each method, writers are expected to be able to produce articles that are quality, relevant, and under academic rules. This education is expected to be a practical guide for students, researchers, and academics in developing the ability to write scientific articles.